Scientific background of the selection program in the Latxa breed - Ugarte E.; Legarra A. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
This paper presents the genetic parameters of the new traits that have been studied in the Latxa breed: milk composition traits (fat and protein contents), udder morphology traits (udder depth and attachment and teat size and length) and Somatic Cell Count (SCC). Except for protein content that shows an estimated heritability of 0.47, for milk composition traits the heritabilities are slower that those obtained in other breeds like Churra, Manchega, Sarda and Lacaune. For udder traits, the heritabilities are in the same range as those obtained for other breeds and for SCC the estimated heritabilitiy is lower that in other breeds. In general there are large differences between results obtained in different breeds. They show that, in the Latxa breed, the new traits have genetic variance that can be exploited. The control of composition traits, SCC and udder morphology will continue but with different aims for each type of trait.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)